THE EFFECT OF CHRONIC EXPOSURE TO CADMIUM AND ZINC ON THE HEMATOLOGICAL PARAMETERS OF Cirrhinus mrigala (Journal of Medical & Health Sciences Review, 2025)
Heavy metals are among the major environmental contaminants responsible for the degradation of aquatic ecosystems, largely due to human and anthropogenic activities. The present study investigated the impact of chronic cadmium (Cd) and zinc (Zn) exposure on the hematological parameters of Cirrhinus mrigala. Fingerlings were acclimatized for two weeks under laboratory conditions before being exposed for 60 days to three treatment levels: T1 (1/3rd LC₅₀), T2 (1/5th LC₅₀), and T3 (1/7th LC₅₀) of Cd and Zn, while a control group was maintained without metal exposure. Hematological indices, including red blood cells (RBCs), white blood cells (WBCs), hemoglobin (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC), were analyzed. Results revealed a significant decline in Hb, RBCs, and Hct values, while WBC counts increased markedly. Alterations in MCV, MCH, and MCHC further indicated morphological and functional disruptions in erythrocytes. These findings demonstrate the potential of hematological parameters as reliable biomarkers for assessing metal-induced stress in fish and highlight the ecological risks associated with heavy metal contamination in aquatic systems.